A iconicidade e a aquisição de palavras do português - Ananias, Thayná Cristina (2024)
Iconicity is a widely researched linguistic aspect by different areas (linguists, biologists, psychologists, etc.) and by different theories within a specific area, such as linguistics (formalism and functionalism, for example). Therefore, the concept attributed to iconicity also touches on different particularities. Specifically for this research, we understand it as a similarity between linguistic form (whether written, sound or gestural) and referent (as object, feeling, action, etc.). As far as we know, there is not yet a research that investigates iconicity in the Brazilian Portuguese (BP) lexicon, so we aim to fill this gap. Thus, we propose to replicate the experiment by Perry, Perlman and Lupyan (2015) and collect the iconicity rating for a sample of 529 BP words. The authors whom we are based seek to investigate, mainly, the relationship between iconicity rating, lexical category and age of acquisition of words in English and Spanish. The results by Perry, Perlman and Lupyan (2015) indicate that words with higher scores for iconicity, both in English and in Spanish, also show a higher percentage of learning by children aged up to 30 months, i.e., words learned more easily also have a higher iconicity score. Perry, Perlman and Lupyan (2015) also consider a typological hypothesis in their conclusion: languages that present similar linguistic structural patterns will present similar results in experiments like these. It is expected that the results in Spanish are in line with those in Portuguese, since these are languages whose verbs represent the direction of action, and the surrounding words can represent the mode of action (verb-framed languages). To investigate and relate these issues to Portuguese, we replicated the authors' experiments. Our results confirm the indications of English and Spanish: more easily learned words also have a higher iconicity score in BP. As for the relationship between iconicity ratings and lexical category, as well as in English and Spanish, the categories with the highest ratings in BP were onomatopoeias and interjections, followed by adjectives. However, they did not follow the expectation of the typological hypothesis indicated by the authors: there was no significant difference between verbs and nouns in Spanish; on the other hand, verbs obtained higher scores than nouns in BP, as well as in English.